Pengaruh Konsentrasi Mikroorganisme Lokal (MOL) dari Rebung Bambu terhadap Pertumbuhan Vegetatif Tanaman Ubi Kayu (Manihot esculenta Crantz) - SETYANINGRUM, LARAS; ASTAWA, I NYOMAN GEDE; MAYUN, IDA AYU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2023)
The Effect of Concentration of Local Microorganisms (Mol) From Bamboo Shoots on the Vegetative Growth of Cassava ( Manihot esculenta Crantz) Cassava ( Manihot esculenta Crantz) is a multipurpose plant because the stems, leaves, and tubers can be used. This study aimed to determine the effect of the MOL concentration of bamboo shoots on the growth of cassava plants. The research was carried out from January to April 2022 at the Experimental Garden of the Faculty of Agriculture, Udayana University. The study used a Randomized Block Design (RBD) with one factor, which is the concentration of MOL with 4 levels of treatment, namely, control (P 0 ), 60 ml/L of water (P 1 ), 80 ml/L of water (P 2 ) and 100 ml/L of water (P 3 ). Each treatment was repeated six times, so the total treatment unit was 24 treatments. The results showed that the mole treatment of bamboo shoots on the growth of cassava significantly affected the shoot length, number of roots; has significant effect on the variable shoot emergence time and length of the root and an insignificant effect on the variables of the number of shoots, number of leaves and leaf chlorophyll. MOL of bamboo shoots with a concentration of 60 ml/L of water gave the highest yield on all variables, namely the fastest shoot emergence time (9.17 DAP), the highest shoot length (56.83 cm), the highest number of shoots (2.17 piece), the highest number of leaves (34.83 strands), the highest leaf chlorophyll (42.40 SPAD), the highest number of roots (20.33 piece) and the highest root length (59.17 cm).